Five Connectivity Areas of the China's Belt and Road Initiative - I. Chubarov (Международная аналитика, 2018)
The article strives to go beyond the common understanding of China's BRI strategy as a set of Eurasian logistics corridors and related investment and transportation projects. Scrutinizing the five integration areas (wu tong), namely foreign policy, infrastructure, trade & economic, financial and humanitarian, one can come to the conclusion that it is a set of activities to support the "going out" of the Chinese commercial firms to the leading positions in various sectors of the world economy. Climbing up the value chain by the "national champions" is a necessary condition for China's entrance to the center of the world economy. The arena of action is the periphery and semi-periphery (so called "countries along the belt and road"), where China is gradually pushing out corporations of developed countries.In addition, the strengthening of China's status in the eyes of the international community and the formation of the image of a great power hold independent importance for the people and leadership. Assessing BRI as the next natural stage of China's foreign economic openness policy at the new stage of globalization and at the same time as a self-valuable tool for restoring the country's prestige on the world stage allows more accurate evaluate Chinese intentions in joint projects.